Mosippans (Pulsatilla vernalis L.) reaktion på brandstörning - Nygårdh, Julia (2022)
Spring Pasque Flower, Pulsatilla vernalis (L.) Mill, is a perennial plant which grows in open and sandy pine forests. It is considered sensitive to competition and in need of repeated disturbances. In Sweden P. vernalis has declined severely and was assessed as endangered (EN) in the latest Red List. The boreal forest has historically been disturbed by wildfires but in Scandinavia wildfires are rare today and this is thought to have affected many species negatively, including P. vernalis. The aim of this study was to examine survival and growth of P. vernalis after fire disturbance.